Potentially inappropriate prescribing and adverse drug reactions in the elderly: a population-based study - Hedna, Khedidja (Eur J Clin Pharmacol, 2015)
PURPOSE: Potentially inappropriate prescriptions (PIPs) criteria are widely used for evaluating the quality of prescribing in elderly. However, there is limited evidence on their association with adverse drug reactions (ADRs) across healthcare settings. The study aimed to determine the prevalence of PIPs, defined by the Screening Tool of Older Persons’ potentially inappropriate Prescriptions (STOPP) criteria, in the Swedish elderly general population and to investigate the association between PIPs and occurrence of ADRs. METHOD: Persons ≥65 years old were identified from a random sample of 5025 adults drawn from the Swedish Total Population Register. A retrospective cohort study was conducted among 813 elderly with healthcare encounters in primary and specialised healthcare settings during a 3-month period in 2008. PIPs were identified from the Swedish Prescribed Drug Register, medical records and health administrative data. ADRs were independently identified by expert reviewers in a stepwise manner using the Howard criteria. Multivariable logistic regression examined the association between PIPs and ADRs. RESULTS: Overall, 374 (46.0 %) persons had ≥1 PIPs and 159 (19.5 %) experienced ≥1 ADRs during the study period. In total, 29.8 % of all ADRs was considered caused by PIPs. Persons prescribed with PIPs had more than twofold increased odds of experiencing ADRs (OR 2.47; 95 % CI 1.65–3.69). PIPs were considered the cause of 60 % of ADRs affecting the vascular system, 50 % of ADRs affecting the nervous system and 62.5 % of ADRs resulting in falls. CONCLUSION: PIPs are common among the Swedish elderly and are associated with increased odds of experiencing ADRs. Thus, interventions to decrease PIPs may contribute to preventing ADRs, in particular ADRs associated with nervous and vascular disorders and falls. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00228-015-1950-8) contains supplementary material, which is available to authorized users.